It’s about time for untimely action - Benjamin Gagnon Chainey (Revista Internacional de Educação e Saúde, 2023)
Illness, but also caring for the ill and mourning the dead, requires allowing oneself to experience a different time, an embodied untimeliness where different rhythms coexist, removed from the speedy tumult of those for whom health is no immediate concern. Rather than a chronological flow, it is a kairotic time, which is sensitive to the context, and allows wanderings and repetitions, hesitations, and changes in pace[1]. Caring and mourning demands “untimeliness and disadjustment of the contemporary[2].” In that sense, the intimate experience of illness is comparable to a form of creativity.